Discernment of Youth towards E-Retailing in Asian and Gulf Marketing Territories - Mathews, Soney; Varshney, Seema; Jassel, Jagdeep Singh (Business Science Reference, 2016)
Internet has created an opportunities for businesses especially retailers to stay connected with customers in the era of globalization. The customers can make purchase in a faster and convenient manner with the use of internet. E-Retailing is becoming very prominent and is being accepted by every age group across the world over the last few decades.Customers are embracing the shift from physical store to virtual store for purchase of products. E-Commerce has been grown very fast because of many advantages associated with buying on internet because of lower transaction and search cost as compared to other types of shopping. Through online shopping consumers can buy faster, more alternatives and can order product and services with comparative lowest price. (Cuneyt and Gautam 2004). This research paper will focus on youth of different social, national cultural backgrounds and their perception and attitude towards e-retailing. This also attempts to find out the important factors that make them loyal towards a particular marketer, without personal interaction.